Mobilization and oxidative burst of neutrophils are influenced by carbohydrate supplementation during prolonged cycling in humans - Scharhag, J.; Meyer, T.; Gabriel, H. H. W.; Auracher, M.; Kindermann, W. (European Journal of Applied Physiology, 2002)
Prolonged, strenuous exercise may lead to suppressive effects on the immune system, which might be responsible for a greater susceptibility to opportunistic infections. The aim of this study was to examine the influence of carbohydrate substitution (CHS) during prolonged, strenuous exercise on neutrophil granulocytes and their oxidative burst (intracellular oxidation of dihydrorhodamine123 to rhodamine123 after induction by formylized 1-methionyl-1-leucyl-1-phenylalanin) using flow cytometry. In three trials different concentrations of CHS (placebo compared to 6% and 12% CHS; 50 ml·kg-1) were given randomly to 14 endurance trained cyclists [mean (SD) age 25 (5) years, maximal oxygen uptake 67 (6) ml·min-1·kg-1] cycling for 4 h in a steady state at 70% of their individual anaerobic threshold. Blood samples were taken before, immediately after cessation, 1 h and 19 h after exercise. A significant rise in neutrophil counts was observed immediately after cessation and 1 h after exercise with a return to normal rest values 19 h after exercise for all three conditions (P<0.001). The relative proportions of rhodamine123+ neutrophils were significantly diminished in all three conditions 1 h after exercise (P<0.01), while the mean fluorescence intensity was lowest in the placebo trial and differed significantly to the 12% CHS trial (P=0.024) and almost significantly to the 6% CHS trial (P=0.052). In conclusion, these data suggest a beneficial effect of CHS on the neutrophil oxidative burst and a possible attenuation of the susceptibility to infections, presumably due to the reduction of metabolic stress in prolonged, strenuous exercise.